Small-dimensioned Short-lengths of Timber and their Suitability for Structural Purposes - Venkaiya, N. (Indian Forester, 1959)
In the light of new methods of timber construction developed during the past few decades, a rational approach for utilizing the timber resources of the country for strctural purposes is suggested. Small-dimensioned short-lengths of main as well as the secondary species of Indian timbers, ranging from Â¾" Ã— 2" Ã— 2’ 0" to 2" Ã— 6" Ã— 8’ 0" sizes are suggested for structural purposes. The economy of construction as well as the possibilities of improving the availability of structural timbers in the Indian markets have been discussed. The need for standardizing the structural sizes of small-dimensioned stock is also emphasized.